Targeted Genetic Changes in Candida albicans Using Transient CRISPR‐Cas9 Expression. Issue 1 (20th January 2021) - Huang, Manning Y.; Cravener, Max C.; Mitchell, Aaron P.
Abstract: Candida albicans is an opportunistic fungal pathogen responsible for significant disease and mortality. Absent complete mating and other convenient methods, dissection of its virulence factors relies on robust tools to delete, complement, and otherwise modify genes of interest in this diploid organism. Here we describe the design principles and use of CRISPR associated nuclease 9 (Cas9) and single‐guide RNAs transiently expressed from PCR cassettes to modify genes of interest, generating homozygous mutants in a single transformation step. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : PCR amplification of CRISPR components Basic Protocol 2 : Transformation of Candida albicans Basic Protocol 3 : Selecting and genotyping transformants Alternate Protocol 1 : Deletion with recyclable markers by CRISPR induced marker excision (CRIME) Alternate Protocol 2 : Knock‐in and combining multiple cassettes with overlapping homology